Cystatin C: diagnostic and prognostic value in acute kidney injury - D. I. Korabelnikov; M. O. Magomedaliev (Фармакоэкономика, 2024)
Acute kidney injury (AKI) is a life-threatening condition that occupies one of the leading places in the structure of mortality in intensive care units. AKI markers common in clinical practice are characterized by a number of disadvantages: serum creatinine – late response to damage to the kidney tubules, an increase in damage to more than 50% of nephrons; urine volume – limited diagnostic value and overdiagnosis of AKI in dehydration, the impossibility of assessing on the basis of a single measurement, as well as the need for regular and frequent dynamic monitoring. The review considers the diagnostic and prognostic possibilities of cystatin C (CysC) in AKI. The results of 55 researches were analyzed. The influence of a number of physiological conditions and non-renal diseases on blood serum and urinary CysC levels were shown. These indicators proved to be highly sensitive and specific biomarkers for AKI diagnosis and prognosis, allowing the specialists to verify renal dysfunction at an early stage of development, ahead of structural changes, and thereby to timely correct treatment, including withdrawal of nephrotoxic drugs and initiation of nephroprotection therapy.